Discovery and prioritization of genetic determinants of kidney function in 297,355 individuals from Taiwan and Japan - Chen, Hung-Lin; Chiang, Hsiu-Yin; Chang, David Ray; Cheng, Chi-Fung; Wang, Charles C. N.; Lu, Tzu-Pin; Lee, Chien-Yueh; Chattopadhyay, Amrita; Lin, Yu-Ting; Lin, Che-Chen; Yu, Pei-Tzu; Huang, Chien-Fong; et al. (Nature communications, 2024)
Current genome-wide association studies (GWAS) for kidney function lack ancestral diversity, limiting the applicability to broader populations. The East-Asian population is especially under-represented, despite having the highest global burden of end-stage kidney disease. We conducted a meta-analysis of multiple GWASs ( n = 244,952) on estimated glomerular filtration rate and a replication dataset ( n = 27,058) from Taiwan and Japan. This study identified 111 lead SNPs in 97 genomic risk loci. Functional enrichment analyses revealed that variants associated with F12 gene and a missense mutation in ABCG2 may contribute to chronic kidney disease (CKD) through influencing inflammation, coagulation, and urate metabolism pathways. In independent cohorts from Taiwan ( n = 25,345) and the United Kingdom ( n = 260,245), polygenic risk scores (PRSs) for CKD significantly stratified the risk of CKD ( p < 0.0001). Further research is required to evaluate the clinical effectiveness of PRS CKD in the early prevention of kidney disease. Here the authors present a large genetic study in East Asians that identifies 97 genetic regions linked to kidney function. These findings aim at better understanding chronic kidney disease in diverse populations.